2017
DOI: 10.1364/optica.4.000814
|View full text |Cite
|
Sign up to set email alerts
|

All-dielectric nanophotonics: the quest for better materials and fabrication techniques

Abstract: All-dielectric nanophotonics is an exciting and rapidly developing area of nanooptics which utilizes the resonant behavior of high-index low-loss dielectric nanoparticles for enhancing light-matter interaction on the nanoscale. When experimental implementation of a specific all-dielectric nanostructure is an issue, two crucial factors have to be in focus: the choice of a high-index material and a fabrication method. The degree to which various effects can be enhanced relies on the dielectric response of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
333
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(342 citation statements)
references
References 127 publications
5
333
0
4
Order By: Relevance
“…In some way, the search for alternative HRI materials can be compared with that for alternative plasmonic materials. This search started a few years ago with a focus on HRI Mie resonators …”
Section: High Refractive Index Mie Resonancesmentioning
confidence: 99%
“…In some way, the search for alternative HRI materials can be compared with that for alternative plasmonic materials. This search started a few years ago with a focus on HRI Mie resonators …”
Section: High Refractive Index Mie Resonancesmentioning
confidence: 99%
“…Another way to get around the significant loss in plasmonic materials is to replace metallic components of nanophotonic devices by high-index dielectric nanoparticles (NPs), made of, e.g., silicon (Si), germanium (Gi), GaP [32], [33], [42]- [44], [34]- [41], or halide perovskites [45] (hereinafter we define as "dielectric" a material with small conductivity at optical frequencies, i.e., 3 this definition includes semiconductors). It has been demonstrated that such dielectric NPs and nanostructures provide lower dissipative losses along with a moderate light localization at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductors, which are often considered as the main materials for all-dielectric photonics [18] have strong inherent Raman response due to their crystalline lattice structure. In particular, crystalline silicon (Si) has a sharp Raman line around 520 cm −1 [19], caused by the interaction of light with optical phonons.…”
Section: Introductionmentioning
confidence: 99%